2014
DOI: 10.1371/journal.pone.0106066
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Training Load, Salivary Cortisol Responses and Performance during Season Training in Middle and Long Distance Runners

Abstract: PurposeMonitoring training from a multifactorial point of view is of great importance in elite endurance athletes. This study aims to analyze the relationships between indicators of training load, hormonal status and neuromuscular performance, and to compare these values with competition performance, in elite middle and long-distance runners.MethodFifteen elite middle and long-distance runners (12 men, 3 women; age = 26.3±5.1 yrs) were measured for training volume, training zone and session rate of perceived e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 27 publications
3
30
0
4
Order By: Relevance
“…Therefore, reductions in TST and SE may reflect a negative adaptation to training in response to large increases in training load. Heavy training can lead to increases in circulating cortisol96 and sympathetic activity,97 both of which may prevent the normal downregulation of the human stress systems (ie, hypothalamic-pituitary-adrenal, sympathetic-adrenal-medullary) required for healthy sleep 98 99. In support, changes in resting alpha-amylase, a marker of sympathetic activity, have been negatively correlated with changes in SE among synchronised swimmers 65.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, reductions in TST and SE may reflect a negative adaptation to training in response to large increases in training load. Heavy training can lead to increases in circulating cortisol96 and sympathetic activity,97 both of which may prevent the normal downregulation of the human stress systems (ie, hypothalamic-pituitary-adrenal, sympathetic-adrenal-medullary) required for healthy sleep 98 99. In support, changes in resting alpha-amylase, a marker of sympathetic activity, have been negatively correlated with changes in SE among synchronised swimmers 65.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a gold standard method for equalization of training loads in different modalities of exercise (1,2,7,8,28), session RPE can be used mainly because of its validity for monitoring exercise at various ages (1,(8)(9)(10)15). Moreover, this method presents significant correlations with HR, blood lactate concentrations, and cortisol levels at continuous efforts (2,(8)(9)(10)13,15,31).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this method presents significant correlations with HR, blood lactate concentrations, and cortisol levels at continuous efforts (2,(8)(9)(10)13,15,31). Although no study was found using RPE session for equalizing load, this parameter represents the global feeling of exertion experienced during training session, allowing the monitoring of high-intensity exercises, like resistance training in older women (7,8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estes achados podem ser explicados pelo fato de que o cortisol é produzido em maior quantidade em treinos aeróbios prolongados, principalmente para estimular o metabolismo de lipídios e proteínas 35,36 . Nesse sentido, a combinação de exercícios aeróbios prolongados e exercícios intervalados de alta intensidade, são frequentemente realizados por corredores de fundo, o que pode ter contribuído para o aumento do cortisol em relação aos demais grupos [36][37] . Recentemente Balsalobre-Fernández et al 37 encontraram uma associação entre o volume de treinamento (quilômetros percorridos) e a concentração de cortisol salivar em corredores de média e longa duração, demonstrando que, quanto maior o volume de treinamento semanal, maior a concentração de cortisol salivar.…”
Section: Velocistas Fundistas Saltadoresunclassified